Effectiveness of Facial Acupressure Treatment on Reducing Anxiety in Postpartum Mothers at Midwife Sontri’s Practice - Nur Afni (CV. Q2 Lantera Ilmiah Institut, 2025)
Postpartum anxiety is a common psychological condition experienced by mothers after childbirth, which can negatively impact maternal health and the bonding process with the baby. Facial acupressure, a technique that stimulates facial reflex points, is believed to promote relaxation and reduce anxiety levels by improving blood circulation and balancing the parasympathetic nervous system. This study aimed to analyze the effectiveness of facial acupressure treatment in reducing anxiety among postpartum mothers at Midwife Sontri’s Practice. This research employed a quasi-experimental design with a pre- and post-test approach without a control group. The study population included postpartum mothers experiencing mild to moderate anxiety, with a total sample of 30 respondents selected through purposive sampling. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed using the Wilcoxon Signed Rank Test. The results demonstrated a significant reduction in anxiety levels after receiving facial acupressure treatment, with a p-value of 0.001 (p<0.05). Physiologically, stimulation of facial reflex points enhances endorphin secretion and activates the vagal nerve system, which contributes to muscle relaxation and decreased heart rate. In conclusion, facial acupressure is effective in reducing anxiety levels among postpartum mothers and can serve as a non-pharmacological complementary therapy in midwifery care.